HABIB, ISLAM DAN OTORITAS KEAGAMAAN: PENERIMAAN MASYARAKAT MUSLIM BANYUWANGI - Atho'ilah Aly Najamudin; Irwan Abdullah (LPPM IAIN Sultan Amai Gorontalo, 2022)
Abstract: Habib as a descendant of the Prophet Muhammad SAW was accepted as a religious elite group in Banyuwangi. Habib became powerful in informing the congregation. We can find majelis taklim, recitations organized by Habib which tend to have many followers spread over rural or urban areas in Banyuwangi. This study focuses on examining the acceptance of the Muslim community in Banyuwangi to Habib's. This research is qualitative research, interviews, and direct experience of researchers in the Habib group in Banyuwangi after the sources were identified descriptive-analytical. The results showed that the community placed Habib as a preacher, leader of the majelis Taklim, Cultural Broker, Philanthropos, and consoler. This paper concludes that the acceptance of the Muslim community in Banyuwangi is encouraged by Habib having religious authority in spreading power through recitations in attracting the sympathy of the Muslim community.